PENGEMBANGAN GAME EDUKASI INTERAKTIF UNTUK PEMBELAJARAN TAJWID DAN HAFALAN JUZ’AMMA - Putra, Agam Maulana; Bastian, Ade (Universitas Majalengka, 2025)
This study presents the development of an interactive educational game designed to support learning of tajwid and memorization of Juz ’Amma. The game was developed using the Game Development Life Cycle (GDLC) method and implemented with Unity, featuring modules for tajwid theory, examples with audio, and recitation of Juz ’Amma, as well as interactive quizzes. Usability testing was conducted with students at MTs Assalam Cokroaminoto Maja to evaluate ease of use, efficiency, memorability, error rate, and user satisfaction. Results indicate that the game effectively enhances motivation, improves comprehension of tajwid rules, and supports memorization of Juz ’Amma in an engaging and enjoyable way. With positive feedback from users and minimal error rates, this interactive learning media demonstrates its potential as an innovative tool for Islamic education, providing a more dynamic alternative to conventional learning methods. The integration of technology in this context also aligns with the learning needs of the digital generation, making Qur’an education more accessible and relevant.